An Analysis on Reading Activities of an English Textbook Used at Eleventh Grade of SMA Negeri 1 Jambi City in Academic Year 2020/2021 - Faradila Dian Arizal; Suyadi Suyadi; Kartika Dewi (JELT: Journal of English Language Teaching, 2021)
This research aimed to analyze the reading texts provided in English textbook used in SMA N 1 Jambi City based on the criteria of reading text. The criteria are the variety, exploitability, suitability of content, the length or size, readability and authenticity of the text. In this research, the researcher used descriptive qualitative. Specifically, the research method that used in gathering the data is content analysis method. The data were gathered by reading all of the reading texts repeatedly to identify and classify the necessary data. There are seven reading text with different variety which includes narrative, expository, speech, play script and recount text. All of these texts were also provided with reading activities which is split into three phase including pre-reading, while reading and post reading activities. These texts have different topic and theme which also found to be suitable for high schools students. The topic and theme of the text are interesting and can be referred to the other subjects in their learning. However, the length of the texts are seems to be not suitable for high school students. Most of the texts were considered to be more suitable for students in lower level. The texts also met the readability criteria since the topic are familiar to the students and there is no over-detailed or oversimplified explanation within. Finally, the results also show that the texts are met the authenticity criteria, which means most of them are taken from authentic sources that relevant to the topic. Keywords: Reading Activities, Textbook